095 Dialysis patients with infective endocarditis who received valve replacement have improved 1-year survival. (22nd September 2015) - Jones, D A; Matthews, K; McGill, L A; Rathod, K; Yaqoob, M; Ashman, N; Mills, P; Wragg, A
Abstract : Background: The incidence of Infective endocarditis (IE) in dialysis patients is higher than the general population. Dialysis patients who develop endocarditis are thought to have a poorer prognosis. We examined the risk factors and outcome of IE in a dialysis cohort. Methods: A retrospective analysis of all patients developing IE on dialysis (using the Duke criteria) was undertaken between 1998 and 2008. Patients were identified using a prospectively collected clinical database. Results: Thirty patients developed IE out of a total dialysis population of 1500 (incidence 2% year; normal population 0.003–6%). The overall 1-year survival was 50%. Ninety three per cent (28/30) patients were on long-term haemodialysis (HD) and 7% (2/30) on peritoneal dialysis (PD). Mean patient age was 59 years (range: 32–87), and mean duration of HD prior to IE was 34 months. Primary HD access was an arteriovenous fistula in 32% (9/28), a dual-lumen tunnelled catheter in 54% (15/28), and a dual-lumen non-tunnelled catheter in 14% (4/28). Staphylococcus aureus (SA) (including MRSA) was present in 47% (14/30). The aortic valve was affected in 47% (14/30) of patients, mitral valve in 27% (6/30) of patients, and both valves in 10% (3/30). Thirty-six per cent of patients had an abnormal valve before the episode of IE. In 20% (6/30) valve surgery was performed and survival was 83% at discharge and was maintained at 1 year (abstract 095 figure 1 ). In 80% (24/30) antibiotic therapy alone was employed and survival was 83% (20/24) at discharge, but only 38% (9/24) at 1 year. Age >60, septic emboli and MRSA were all adverse prognostic factors. Patients receiving surgery were younger (mean 56 vs 61) and less likely to be infected with SA (surgery 29% vs antibiotics 70%). Conclusions: This is one of the largest reported series of IE in dialysis patients. The incidence of IE remains high and the prognosis poor in dialysis patients, although patients selected for early valve surgery have good 1-year survival.